The Influence of Motivation and Anxiety on the Students' Speaking Performance in Online Learning - Devi Mufidah Juhriyah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
The aim of this study was to find out the influence of motivation and anxiety on the students’ speaking performance in online learning that can help the students to get an optimal result in speaking. The subject of this study was 98 students from the third year English education department of University of Islam Malang. The instruments used in this study were questionnaire and documentation. The questionnaires were Attitude/Motivation Test Battery (AMTB) and Foreign Language Anxiety Scale (FLCAS). Also, the documentation instrument was in the form of students’ final score of Speaking III class. The results showed that the first finding obtained a significance value (0.002), which means that there was a significant influence of the motivation on the students’ speaking performance. Meanwhile, the second finding obtained a significance value (0.001) and tcount (-3.52). However, the second finding has to be decided using the side left of the hypothesis test because the tcount obtained was negative. Then, it showed that there was a significant influence of the anxiety to the students’ speaking performance. The third finding was obtained Fcount (13.019) and significant value (0.000), it can be said that there was a significant influence between motivation and anxiety simultaneously on the students’ speaking performance in online learning. Keywords: Speaking, Speaking Performances, Motivation, AnxietyThe aim of this study was to find out the influence of motivation and anxiety to the students’ speaking performance in online learning that can help the students to get an optimal result in speaking. The subject of this study was 98 students from the third year English education department of University of Islam Malang. The instruments used in this study were questionnaire and documentation. The questionnaires were Attitude/Motivation Test Battery (AMTB) and Foreign Language Anxiety Scale (FLCAS). Also, the documentation instrument was in the form of students’ final score of Speaking III class. The results showed that the first finding obtained significance value (0.002), it means that there was a significant influence of the motivation to the students’ speaking performance. Meanwhile, the second finding obtained significance value (0.001) and tcount (-3.52). However, the second finding have to be decided using the side left of the hypothesis test because the tcount obtained was negative. Then, it showed that there was a significant influence of the anxiety to the students’ speaking performance. The third finding were obtained Fcount (13.019) and significant value (0.000), it can be said that there was a significant influence between motivation and anxiety simultaneously to the students’ speaking performance in online learning. Keywords: Speaking, Speaking Performances, Motivation, Anxiety